Potential influences of exogenous pollutants occurred in waste activated sludge on anaerobic digestion: A review - Luo, Jingyang; Zhang, Qin; Zhao, Jianan; Wu, Yang; Wu, Lijuan; Li, Han; Tang, Min; Sun, Yaqing; Guo, Wen; Feng, Qian; Cao, Jiashun; Wang, Dongbo (Journal of hazardous materials, 2020)
[Display omitted] •The exogenous pollutants exhibit dose-dependent influences on sludge digestion.•Methanogens are vulnerable to the exogenous pollutants in WAS.•The pollutants influences on WAS digestion and underlying mechanisms are concluded.•The synergistic effects of multiple pollutants on WAS digestion is less known. Anaerobic digestion is a promising approach for waste activated sludge (WAS) disposal. However, a wide range of exogenous pollutants (e.g. heavy metals, nanoparticles) exists in WAS and their influences on anaerobic digestion are neglected. This study investigates the correlations between exogenous pollutants and anaerobic digestion performance. The results indicate that exogenous pollutants exhibit dose-dependent influences on WAS digestion. Most of the pollutants improve the performance of anaerobic digestion by partially or wholly promoting the hydrolysis, acidification and methanogenesis processes at low dose, but exhibit negative effects at high levels due to their toxicity. Generally, methanogens are more vulnerable than those hydrolytic and acidogenic bacteria. Poly-aluminum chloride and polyacrylamide show strong inhibition on WAS digestion, which are primarily attributed to their physical enmeshments of organic matters in WAS. The synergistic effects of different mixed pollutants and the mitigating strategies for typical pollutants inhibition deserve more attention in light of WAS anaerobic digestion.